THE FUNCTION OF METONYMY IN THE FORMATION OF LANGUAGE MEANING - Josua Silalahi; Bernieke Anggita Ristia Damanik (Journal of English Education and Literature, 2025)
Metonymy is one of the important figures of speech in the process of forming meaning in verbal communication. This paper discusses the function of metonymy as a tool to convey meaning effectively and efficiently in everyday language as well as in rhetorical and cultural contexts. Through a semantic approach, this study explains how metonymy helps enrich messages by replacing a word or phrase with a term that has a close association relationship. The main functions of metonymy include accelerating the communication process, creating an interesting stylistic effect, and facilitating the delivery of complex meanings simply. In addition, metonymy also plays an important role in shaping social and cultural perceptions through the use of terms that represent certain institutions or concepts, for example the use of "istana" to refer to the government. This paper uses literature studies and analysis of examples in Indonesian to show various forms of metonymy and their roles. Thus, this paper is expected to provide a deeper understanding of the function of metonymy in forming language meaning as well as being a reference for further linguistic and semantic studies.